The Effect of Using Classcraft on EFL Students’ Reading Comprehension - Muhamad Laudy Armanda; Lilia Indriani (Metathesis: Journal of English Language, Literature, and Teaching, 2023)
Students nowadays are considered as the generation who have never known the world without video games, cell phones, and the internet. Hence, gamification has become a solution. It is a method that can boost the students' mood during lectures, so they feel enjoy during the learning process. In short, this study aims to examine whether using Classcraft has a significant effect on the reading comprehension of EFL students. This study was classified as a pre-experimental study (N=37), followed by assessing their reading comprehension. Two-session treatment began, which included teaching reading comprehension using Classcraft. At the end of the course, a reading post-test was administered. The findings propose a statistically significant difference in the pre-test and post-test scores for the treatment group. By implementing Classcraft’s features allows EFL students to be more competent in English reading comprehension, especially in making inferences and encouraging them through gamified learning. The current study offered empirical evidence of how reading instruction using Classcraft promoted EFL students’ reading comprehension.